Test of rolling stock electromagnetic compatibility for cross‐domain interoperability. Issue 1 (1st February 2016) - Karadimou, Eva; Armstrong, Rob
Abstract : This study is part of a greater body of research on the electromagnetic compatibility in the railway environment throughout Europe. In particular, this study focuses on the broadcasting services as a victim area and identifies the electromagnetic interference threats in the railway environment. After the definition of the pantograph arcing as the worst‐case scenario in terms of interference to these services, a test method was carried out in a controlled environment in order to examine the characteristics of these transient arcing events. It was found out that the power radiated is a broadband signal and the high levels of the radiated emissions require further investigation and examination, including addition to the railway standards that define the cross‐domain interoperability of equipment, rolling stock and fixed installations in the railway environment.